What did we do to our mountain? African eco-feminist and indigenous responses to cyclone Idai in Chimanimani and Chipinge districts, Zimbabwe - Chirongoma, Sophia; Chitando, Ezra (The African Journal of Gender and Religion, 2022)
Cyclone Idai caused untold devastation in Chimanimani and Chipinge districts, Zimbabwe. In scenes reminiscent of the biblical deluge, in some places entire settlements were eradicated from the face of the earth. Houses were swept away, bodies were submerged and water, typically understood as the source of life, became the source of death. Individuals, families, communities and nations were left traumatized, and the search for meaning continues. Inevitably, religion featured prominently in explanations of this tragedy. This article is a preliminary review of the explanations of Cyclone Idai in Chimanimani and Chipinge districts, Zimbabwe, within the frame of African Traditional Religion/s (ATR/s) and Christianity. The article delves into questions at the interface of climate change and religion, such as: how do survivors of the cyclone explain its occurrence? What do we learn about the interface between religion and climate change in Africa from the responses to Cyclone Idai in Chimanimani and Chipinge districts? The article adopts the African ecofeminist perspective. This is informed by the fact that women and girls comprise the bulk of the population heavily impacted by Cyclone Idai in Chimanimani and Chipinge as well as the fact that they are the ones who were in the forefront of mitigating the impact of devastation caused by this ecological catastrophe. Our article seeks to contribute to the ongoing scholarly discussions on the nexus between religion, gender and climate change by foregrounding the experiences of women and girls affected by Cyclone Idai. The first part of the article describes the devastation caused by Cyclone Idai. The second part outlines the Christian and indigenous interpretations of the cyclone. The third part of the article teases out the indigenous interpretations of unpredictable weather patterns.